2016
DOI: 10.3329/bmj.v43i3.26294
|View full text |Cite
|
Sign up to set email alerts
|

Diseases pattern in the department of physical medicine & rehabilitation in a tertiary level hospital

Abstract: This is a retrospective study carried out at the department of Physical Medicine and Rehabilitation in Dhaka Medical College Hospital (DMCH)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A Uniform Data System (UDS) for Medical Rehabilitation is maintained in USA and published annually. No such system exists in Bangladesh 5 . In this study it has been tried to find out the age, sex, occupation, residency and disease pattern of the stroke patients attending in the Department of PMR.…”
Section: Discussionmentioning
confidence: 99%
“…A Uniform Data System (UDS) for Medical Rehabilitation is maintained in USA and published annually. No such system exists in Bangladesh 5 . In this study it has been tried to find out the age, sex, occupation, residency and disease pattern of the stroke patients attending in the Department of PMR.…”
Section: Discussionmentioning
confidence: 99%
“…12 Another one showed most (23.36%) of were between 40-49 years. 10 It was also found in a study, 49.9% were in 41-50 years age. 11 The majority of the patients had PLID (21.60%) and, 10.99% stroke, cervical spondylosis 11.15%, lumbar spondylosis 11.52%, frozen shoulder 10.83%, low back pain 9.49%, osteoarthritis 8.25%, facial palsy 0.43%, rheumatoid arthritis 5.47%, seronegative SpA 0.26%, GBS 0.10%, acute neck sprain/strain 5.68% and others 4.18%.…”
Section: Discussionmentioning
confidence: 57%
“…A cross sectional study at community level for detection of painful musculoskeletal disorders showed that musculoskeletal complaints are predominant in females. 10 Another study in Rangpur Medical College Hospital (RpMCH) also demonstrated 55.1% were female patients. 11 This may be due to increased literacy rate and awareness among female patient.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…No such system exists in Bangladesh. 6 In this study it has been tried to find out the age, sex, occupation, residency and disease profile of patients with FP attending the department of PMR, NINS.…”
Section: Discussionmentioning
confidence: 99%